POTENSI KANDUNGAN UNSUR KIMIA EKONOMIS PADA LARUTAN PANAS BUMI DENGAN STUDI KASUS DI PLTP DIENG, KABUPATEN WONOSOBO DAN KABUPATEN BANJARNEGARA, PROVINSI JAWA TENGAH: THE POTENTIAL CONTENT OF ECONOMIC CHEMICALS ELEMENT IN GEOTHERMAL SOLUTIONS WITH A CASE STUDY IN THE DIENG GEOTHERMAL POWER PLANT, WONOSOBO REGENCY AND BANJARNEGARA REGENCY, CENTRAL JAVA PROVINCE - Sabtanto Joko Suprapto; Suparno; Umi Yuliatin (Buletin Sumber Daya Geologi, 2020)
The Geothermal fluid has a very high content of dissolved elements. Geochemical methods are used to determine the potential indication of dissolved economic elements. Geothermal exploration has been carried out throughout Indonesia, mainly by the Geological Agency. The exploration result in the existence of hot spring data by analyzing SiO2, Al, Fe, Ca, Mg, Na, K, Li, As, NH4, B, F, Cl, SO4, HCO3, and CO2. Base on the secondary data of 256 locations of hot spring in Indonesia that were statistically analyzed, an overview of the association of economic elements and impurities elements is obtained. Dieng Geothermal Power Plant with that has recuring problem of silica scale formation, becomes an interesting object as a case study of the potential of dissolved economic elements. The increase in dissolved content in geothermal fluids apart from naturally occurring, is triggered even more strongly by the geothermal power plant operating system, which changes the liquid phase to the vapor phase, hence the remaining liquid phase more concentrated. The potential content of economic chemical elements is determined by discharge measuring of the remaining liquid phase produced and the results of the analysis of the element concentration dissolved. The results of geochemical data clustering of hot springs obtained four elemental association, the association of SiO2-F, Al-Fe-SO4, Ca-Mg-Cl-Na-K, and Li-B-HCO3. Dissolved lithium content is high in several geothermal areas in Indonesia, found in hot springs with chloride type fluids. The brine produced from the reservoir at the Dieng Geothermal Power Plant is from a meteoric type fluid that has intensively reacted with the surrounding rock and a magmatic type fluid. The remaining brine that is from several separators and comes out through the silencer, at the Dieng Geothermal Power Plant has a total discharge of 457.1 m3/hour, contains high levels of several elements, lithium 77.31-99.4 mg/l, silica 1109.25-1220.9 mg/l, boron 404.16-589.4 mg/l, potassium 2532.2-4536.5 mg/l, and manganese 5.49-15.82 mg/l.